Application of Doctor-Nurse-Patient Co-Decision-Making Nursing Intervention Based on Evidence-Based Problems in the Rehabilitation of Acute Ankle Lateral Collateral Ligament Injury. (19th August 2022) - Wei, Nian; Du, Yuehui; Chen, Shiyu
Abstract : Objective . The aim of this study is to study the application effects of doctor-nurse-patient co-decision-making nursing intervention based on evidence-based problems in the rehabilitation of acute ankle lateral collateral ligament injury. Methods . 150 patients with acute ankle lateral collateral ligament injury who were treated in the hospital between December 2020 and December 2021 were selected, and they were divided into the routine group and the evidence-based group by the random number table method, with 75 cases in each group. The patients in the routine group received routine nursing intervention, while the patients in the evidence-based group adopted doctor-nurse-patient co-decision-making nursing intervention based on evidence-based problems, and both groups were intervened for 1 month. The rehabilitation time (swelling subsidence time, fixation removal time, and normal walking time), ankle active range of motion (dorsiflexion and plantar flexion), ankle function (ankle Kofoed score) before and after intervention, and the total incidence rate of complications (tendon injury, ankylosis, and traumatic arthritis) within 1 month of intervention were compared between the two groups of patients. Results . The swelling subsidence time, fixed removal time, and normal walking time in the evidence-based group were significantly shorter than those in the routine group (P < 0.05 ). After 1 month of intervention, the ranges of motion of dorsiflexion and plantar flexion and ankle Kofoed scores of the two groups were significantly higher than those before intervention, and the abovementioned indicators in the evidence-based group were significantly higher than those in the routine group (P < 0.05 ). Within 1 month of intervention, the total incidence rate of tendon injury, ankylosis, and traumatic arthritis was significantly lower in the evidence-based group than that in the routine group (P < 0.05 ). Conclusion . Nursing intervention of doctor-nurse-patient co-decision-making based on evidence-based problems in patients with acute ankle lateral collateral ligament injury can promote postoperative rehabilitation and restore the ankle function of patients.